2016
DOI: 10.1007/s00405-016-4302-0
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors for central lymph node metastasis in cN0 papillary thyroid microcarcinoma: a meta-analysis

Abstract: Although there have been many studies identifying clinical and pathologic factors that may predict central lymph node metastases (CLNM) in papillary thyroid microcarcinoma (PTMC) patients without clinically cervical lymph node metastasis (cN0), the results were inconsistent. And whether prophylactic central lymph node dissection (pCLND) should be performed in cN0 PTMC remains controversial. The EMBASE, PubMed, MEDLINE and the Cochrane Library were searched until Oct 2015 to identify relevant studies. Primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 46 publications
7
36
3
5
Order By: Relevance
“…Another study by Siddiqui et al (28) showed that younger age (age < 45 years), multifocality, and extrathyroidal extension were predictors of CLNM. Our data showed that male sex and tumor size were not predictive for CLNM, in contrast to findings by others (18,29,30). In addition, Siddiqui et al reported that the risk of lymph node metastasis in incidental PTMC was not significantly different compared with known/suspected PTC (28).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Another study by Siddiqui et al (28) showed that younger age (age < 45 years), multifocality, and extrathyroidal extension were predictors of CLNM. Our data showed that male sex and tumor size were not predictive for CLNM, in contrast to findings by others (18,29,30). In addition, Siddiqui et al reported that the risk of lymph node metastasis in incidental PTMC was not significantly different compared with known/suspected PTC (28).…”
Section: Discussioncontrasting
confidence: 98%
“…Central lymph node metastasis is still a risk in patients with PTC or PTMC; we found that 29.5% of all patients had CLND. Despite the fact that many studies have shown that lymph node metastasis in PTMC is one of the main predictors of recurrence (18)(19)(20), there is no consensus as to whether prophylactic neck dissection should be routinely included in the surgical treatment. The American Thyroid Association guidelines recommend inclusion of neck dissection for PTC only in the setting of clinically evident lymph node metastasis (21).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, papillary thyroid carcinoma (PTC) is the most common thyroid malignancy, accounting for 80-90% of all thyroid malignant tumors [7][8][9]. As with thyroid carcinomas in general, the prognosis of PTC is favorable, and the ten-year survival rate of the classical subtype of PTC (CSTPTC) is over 90% [9].…”
Section: Introductionmentioning
confidence: 99%
“…Multifocality also frequently exhibits in PTC. Certain studies have indicated that multifocal carcinoma in PTC is positively associated with the incidence of CLNM [14,15], while other studies have argued that there is no association between multifocality and CLNM [16]. In addition, multifocality has found to significantly increase the incidence of recurrence [17].…”
mentioning
confidence: 99%